(untitled) (Proceedings of the Institute of Biology, 2021)
Studying the genetic diversity of Mongolian Argali sheep populations using microsatellite loci requires an accurate and world-standard method than Polyacrylamide gel electrophoresis (PAGE). Therefore, in this study, we developed a multiplex PCR for 3 high polymorphism loci (BM302, INRA040, BM4505) using fluorescent labeled primers (FAM, HEX, TAMRA), and tested the usability of this methodology to simultaneously amplify the alleles of multiple micro[1]satellite loci in a short amount of time. Using our multiplex PCR method, the alleles of those 3 loci were successfully amplified on a total of 99 samples from the Altai, Gobi, Khangai, and Khoridol Saridag populations, and their allele lengths were determined by the fragment analysis method. General genetic parameters were evaluated to determine the observed length of alleles on each microsatellite locus that was suitable for research. The number of alleles (Na) observed in Altai (15.00), Gobi Desert (16.67), and Khangai (13.33) populations were relatively high, while in the Khoridol Saridag population, it was lower (9.00). The number of effective alleles (Ne) was comparatively low in Altai (6.73), Gobi Desert (8.02), and Khoridol Saridag (4.2) populations, but considerably uniform in the Khangai population (9.94). Moreover, observed (Ho) and expected heterozygosity (He) was highest in Altai (0.80, 0.84), Gobi (0.74, 0.87), and Khangai (0.85, 0.89) populations. Although the genetic diversity of the BM302, BM4505, and INRA040 loci was high, the majority of the detected alleles had low frequency. In conclusion, multiplex PCR was successfully optimized and the amplified fragments were analyzed which resulted in preliminary population genetic results in a short period. Future research uti[1]lizing this multiplex PCR and fragment analysis methodology should be conducted with more microsatellite markers, leading to precise results concerning the conservation genetics of Argali sheep. Монгол орны аргаль хонины популяцуудын микросателлитын судалгаанд мультиплекс ПГУ ба фрагментийн анализын аргазүйг тогтворжуулан туршсан дүнгээс Монгол орны аргаль хонины генетик олон янз байдлыг микросателлитын локусуудаар судлахад ПААГ-аас илүү өндөр нарийвчлалтай, дэлхийн стандартад нийцсэн фрагмент анализын аргазүйгээр хийх шаардлага тулгарсан. Ингэхдээ олон микросателлитын локусын аллелийг богино хугацаанд олшруулахын тулд бид флуоресценц 3 өөр өнгөтэй (FAM, HEX, TAMRA) бодисоор тэмдэглэсэн праймераар полиморфизм өндөртэй 3 локусыг (BM302, INRA040, BM4505) сонгон мультиплекс ПГУ-ын арга зүй боловсруулж, энэ аргазүйг цаашид ашиглах боломжийг турших зорилгоор энэ судалгааг хийв. Боловсруулсан мултиплекс ПГУ-ын арга зүйг ашиглан Алтай, Говь, Хангай, Хорьдол Сарьдагийн популяцуудын нийт 99 дээжид дээрх 3 локусын аллелиудыг амжилттай олшруулж, аллелийн уртыг тодорхойлсон. Түүнчлэн микросателлитын локус бүрийн аллелиудын урт нь судалгаанд ашиглахад тохиромжтой эсэхийг шалган ерөнхий генетик үзүүлэлтүүдийг тооцоход ажиглагдсан аллелийн тоо Алтай (15.00), Говь (16.67), Хангайн (13.33) популяцад их, Хорьдол Сарьдагийн популяцад харьцангуй бага (9.00) байв. Эффектив аллелийн тоо Алтай (6.73), Говь (8.02), Хорьдол Сарьдагийн (4.2) популяцад хэт бага, Хангайн (9.94) популяцад харьцангуй жигд, хүлээгдэж буй гетерозигот байдал Алтай (0.80, 0.84), Говь (0.74, 0.87), Хангайн (0.85, 0.89) популяцад хамгийн өндөр байв. BM302, BM4505, INRA040 локусуудын генетик олон янз байдал өндөр ч ихэнх аллелиуд нь бага давтамжтай байв. Үүнээс дүгнэхэд, энэхүү боловсруулсан мултиплекс ПГУ амжилттай тогтворжсон бөгөөд олшруулсан бүтээгдэхүүнд фрагмент анализ хийн генетик үзүүлэлтүүдийг тооцож богино хугацаанд популяцийн генетикийн судалгаанд ач холбогдолтой урьдчилсан дүнг гарган авав. Цаашид мултиплекс ПГУ, фрагмент анализийн энэ арга зүйг ашиглан микросателлитын маркеруудын тоог нэмэгдүүлэн судалгааг үргэлжлүүлж аргалийн хамгааллын генетикийн илүү үнэн зөв дүгнэлт гаргах боломжтой гэж үзэв. Түлхүүр үгc: мултиплекс ПГУ тогтворжуулалт, популяцын генетик үзүүлэлт, микросателлит BM302, BM4505, INRA040 локус, аргаль хонь